2016
DOI: 10.1021/acs.est.6b00030
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring Personal Exposure to Organophosphate Flame Retardants Using Silicone Wristbands and Hand Wipes

Abstract: Organophosphate flame retardants (PFRs) are widely used as replacements for polybrominated diphenyl ethers in consumer products. With high detection in indoor environments and increasing toxicological evidence suggesting a potential for adverse health effects, there is a growing need for reliable exposure metrics to examine individual exposures to PFRs. Silicone wristbands have been used as passive air samplers for quantifying exposure in the general population and occupational exposure to polycyclic aromatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
214
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(232 citation statements)
references
References 41 publications
13
214
5
Order By: Relevance
“…9,2022 A recent epidemiological study found a significant association between the urinary metabolite of ITPs and decreases in successful pregnancy outcomes. 23 Identification of the predominant ITP and TBPP isomers in commonly used commercial flame retardant mixtures will aid in hazard characterization and the ongoing, prioritized risk assessment of these compounds by the U.S. EPA.…”
Section: Resultsmentioning
confidence: 99%
“…9,2022 A recent epidemiological study found a significant association between the urinary metabolite of ITPs and decreases in successful pregnancy outcomes. 23 Identification of the predominant ITP and TBPP isomers in commonly used commercial flame retardant mixtures will aid in hazard characterization and the ongoing, prioritized risk assessment of these compounds by the U.S. EPA.…”
Section: Resultsmentioning
confidence: 99%
“…As mixed-media samplers, the calculation of environmental concentrations is difficult, but wristbands can be used to evaluate relative exposures over the time worn [34, 45, 46]. Recent work showed concentrations of organophosphate flame retardants and polycyclic aromatic hydrocarbons (PAHs) in wristbands correlated with urinary metabolites of those compounds [47], which support a link between the ambient personal environment sampled by the wristbands and the internal environment.…”
Section: Discussionmentioning
confidence: 99%
“…The major limitation of our sampling method is that external rather than internal exposures to pesticides are measured. Although studies show correlation between wristband sampling and urine detections [47], there is a growing interest to integrate exposure detections with toxicology bioassays, as implemented here with DNA damage measures.…”
Section: Discussionmentioning
confidence: 99%
“…Like TDCIPP, exposure to TCIPP is also widespread. The hydroxylated metabolite of TCIPP has been ubiquitously detected in humans in several recent studies (Hammel et al, 2016; Van den Eede et al, 2015, 2013). Components of FM550 have been associated with endocrine and metabolic disruption in exposed rodents, and they have been shown to bind and activate nuclear receptors that regulate adipogenic pathways in in vitro models (Belcher et al, 2014; Fang et al, 2014; Patisaul et al, 2013; Pillai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%